Outpatient Antibiotic Prescribing for Older Adults in the United States: 2011 to 2014. Issue 10 (17th September 2018) - Kabbani, Sarah; Palms, Danielle; Bartoces, Monina; Stone, Nimalie; Hicks, Lauri A.
Abstract : Objectives: To characterize antibiotics prescribed to older adults to guide efforts to improve antibiotic use. Design: Descriptive analysis. Setting: Ambulatory. Participants: Adults aged 65 and older in the United States. Measurements: Information on outpatient antibiotic prescriptions dispensed for older adults from 2011 to 2014 was extracted from the IQVIA Xponent database. A chi‐square trend analysis was conducted to assess annual changes in antibiotic prescribing rates. A descriptive analysis of prescribing rates by antibiotic, age group, sex, state, Census region, and provider specialty was conducted. Results: From 2011 to 2014, outpatient antibiotic prescribing rates remained stable in older U.S. adults ( P = .89). In 2014, older adults were dispensed 51.6 million prescriptions (1, 115 prescriptions/1, 000 persons). Persons aged 75 and older had a higher prescribing rate (1, 157 prescriptions/1, 000 persons) than those aged 65 to 74 (1, 084 prescriptions/1, 000 persons). Prescribing rates were highest in the South 1228 prescriptions/1, 000 persons) and lowest in the West (854 prescriptions/1, 000 persons). The most commonly prescribed class was quinolones, followed by penicillins and macrolides. Azithromycin was the most commonly prescribed drug, followed by amoxicillin and ciprofloxacin. Internists and family physicians prescribed 43% of antibiotic courses. Conclusion: On average, in 2014, U.S. adults aged 65 and older received enough outpatient antibiotic courses for every older adult to receive at least 1. Quinolones and azithromycin are potential targets for assessing the appropriateness of antibiotic prescribing in this population. Interventions to improve use targeting internists and family physicians in the South Census region might have the potential to have the greatest effect.